2003
DOI: 10.1046/j.1365-2141.2003.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B‐receptor mutations in Pelger–Huët anomaly

Abstract: Summary. Pelger-Huët anomaly is an inherited abnormality of neutrophils, characterized by reduced nuclear segementation and an apparently looser chromatin structure. Following linkage studies in two families, the lamin B-receptor (LBR) was sequenced and mutations found: CCGfiCTG causing prolinefileucine in codon 119 of exon 3, and IVS11-9 AfiG, disrupting the splice acceptor site. The LBR gene (LBR) was also sequenced from a single English man with Pelger-Huët anomaly and a heterozygous CfiG mutation was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 8 publications
0
33
0
2
Order By: Relevance
“…All of the analyzed mutations producing HEM/Greenberg dysplasia are in the C-terminal sterol reductase region of LBR; 93,99,102 but many of the mutations of the proven PHA (including the surviving homozygous male adult) are also in the sterol reductase region. 84,103 Table 2 presents a list of published PHA and HEM/Greenberg dysplasia mutation sites.…”
Section: Lbr Polypeptide Conformations and Conserved Domainsmentioning
confidence: 99%
“…All of the analyzed mutations producing HEM/Greenberg dysplasia are in the C-terminal sterol reductase region of LBR; 93,99,102 but many of the mutations of the proven PHA (including the surviving homozygous male adult) are also in the sterol reductase region. 84,103 Table 2 presents a list of published PHA and HEM/Greenberg dysplasia mutation sites.…”
Section: Lbr Polypeptide Conformations and Conserved Domainsmentioning
confidence: 99%
“…The acquired form is caused by drug administration or infectious diseases (Dusse et al 2010), but this was ruled out due to the absence of clinically ill rabbits and because no treatments were applied in any of cases. On the other hand, as mentioned previously, the congenital form of PHA is caused by mutations in the gene encoding the lamin B receptor which affect the structure of this protein (Hoffmann et al 2002;Best et al 2003). This receptor is an inner nuclear membrane protein that interacts with heterochromatin, and thus is responsible for the maturation of neutrophil granulocytes (Cohen et al 2007;Hoffmann et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that PHA is a blood laminopathy caused by mutations in genes encoding proteins of the lamin B receptor (Hoffmann et al 2002;Best et al 2003;Schultz et al 2003). The lamin B receptor is required for morphological but not functional maturation of neutrophils (Johanson et al 1980;Cohen et al 2007;Grondin et al 2007;Hoffmann et al 2007); thus, the physiological function of morphologically malformed neutrophils could be intact (Latimer et al 1989).…”
mentioning
confidence: 99%
“…[5] The eleven different mutations occuring in LBR protein resulting in reduced expression is responsible for abnormal morphology of neutrophil in PHA. [4] Yet their life span and function remains normal. [6,7] In case of congenital PHA the percentage of polymorphs with PHA morphology is from 63% to 93%.The cytoplasm is normal .The nuclei is unilobed or bilobed with symmetrical lobes and having lower nuclear-cytoplasmic ratio, and a clumped ,coarse and darkly stained chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported to be occurring in mammals like dogs and cats. [4] Recent studies reveal that PHA occurs as result of quantitative defect in lamin B receptor (LBR) gene located in chromosome 1q41-43. LBR protein is located in the inner nuclear membrane and is responsible for binding of B-type lamins and heterochromatin.…”
Section: Discussionmentioning
confidence: 99%